Diarrhea : causes, types and treatments - Wilson, Hannah M. (Public health in the 21st century series, 2010)
Diarrhoea is a clinical symptom characterised by an increase in the volume, wateriness, or frequency of bowel movements. This book presents research on diarrheal viruses; cholera in Africa; and, the pathogenesis of Clostridium-difficile associated diarrhea